Investigation of Heat Transfer and Pressure Distribution in Power Law Fluids Flowing through a Rectangular Channel Blocked by a Single Heated Circular Cylinder at Inlet. (4th May 2022) - Elhag, S.H.; Memon, Abid A.; Bhayo, Bilawal A.; Bhatti, Kaleemullah; Memon, M. Asif; Jacob, Kavikumar; Bayones, Fatimah S.; Seidu, Jamel
Abstract : In this paper, the flow of a power law fluid has been investigated for Newtonian and non-Newtonian fluids with the temperature distribution in a rectangular channel containing a heated circular cylinder near the inlet with different blockage ratios. The generalized non-Newtonian power law model coupled with the energy equation is solved numerically, considering power law index in the range of 0.8 ≤ n ≤ 1.2 and Reynolds number in the range from 1000 to 10000 . A heated circular cylinder is fixed near the inlet of the channel with blockage ratios (from radius to the height of the channel) of 1 : 10, 2 : 10, and 3 : 10 The governing partial differential equations coupled with energy equation are discretized to investigate the simulation of the current problem with finite element-based software of COMSOL Multiphysics 5.4 . The results are shown with the help of surface plots, tables, and graphs. The computational results for maximum and minimum pressure around the cylinder, temperature along the center line of the cylinder, and local Nusselt number are specially discussed in detail.